Electricity from Peat - Abandoned Plans for a Polish Peat-Fuelled Plant in Wizna : Facts and Contexts - Zawistowski, Andrzej (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The final article explores little-known plans for the use of peat in energy production in Poland. The idea of building a plant in Wizna is shown as part of a wider concept of industrialising rural parts of the country within the Białystok Łomża-Ełk triangle. Repeatedly postponed, the concept never came to fruition, and was finally abandoned after the creation of peat nature reserves in 1967